2009
DOI: 10.1007/s00784-009-0348-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigating interocclusal perception in tactile teeth sensibility using symmetric and asymmetric analysis

Abstract: The purpose of this clinical trial was to determine the active tactile sensibility of natural teeth and to obtain a statistical analysis method fitting a psychometric function through the observed data points. On 68 complete dentulous test persons (34 males, 34 females, mean age 45.9 ± 16.1 years), one pair of healthy natural teeth each was tested: n = 24 anterior teeth and n = 44 posterior teeth. The computer-assisted, randomized measurement was done by having the subjects bite on thin copper foils of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 19 publications
2
39
0
1
Order By: Relevance
“…Furthermore, the range within the 10% and 90% threshold levels gave an estimation of the "certainty" and "precision" of the detection of the interocclusal foil (Enkling et al 2010a(Enkling et al , 2010b.…”
Section: Active Tactile Thresholdsmentioning
confidence: 99%
“…Furthermore, the range within the 10% and 90% threshold levels gave an estimation of the "certainty" and "precision" of the detection of the interocclusal foil (Enkling et al 2010a(Enkling et al , 2010b.…”
Section: Active Tactile Thresholdsmentioning
confidence: 99%
“…Tactile perception was found to depend on the implant surface structure and might point to receptors near the implants as the anatomical basis of osseoperception . Several studies demonstrated that even though the periodontal fiber was missing, the tactile sensibility of the prosthetic restorations would increase when placed on the implants, and that the implant‐supported restorations were superior to soft tissue‐supported restorations with regard to both stability and tactile sensibility . Mericske‐Stern et al concluded that oral function, chewing, and biting of overdenture wearers is similar with support of either implants or natural roots .…”
Section: Discussionmentioning
confidence: 99%
“…DCK has the ability to recognize the direction of movement of a cutaneous stimulus . Graphaesthesia is the perception of figures drawn on the skin . Both of these tests correlate the physiologic function of the receptors to the subjective response of the patient …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations